SARS-CoV-2 multivariable representation in South American countries by using dynamic Biplot and ARIMA modeling infections and lethality - Pilacuan, Luis; Salmon, Beatriz; Gallegos, Diana (EASI: Engineering and Applied Sciences in Industry, 2022)
The coronavirus (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus that has generated a global health crisis. On March 11, 2020, this disease was classified as a pandemic, the most affected regions were Latin America and the Caribbean, due to various factors such as population density, and incapacity in health systems, among others. In this study, a general analysis of the data on infections and deaths from ten South American countries will be carried out, to identify which country has best managed the pandemic according to its contagion and lethality results. A prediction was made for the number of infections and deaths caused by Covid-19, using data reported to the WHO (World Health Organization). The ARIMA model and the dynamic Biplot method were used for this study to represent the analysis. It was found that Peru has a high case fatality rate compared to the countries analyzed, and Peru has a higher number of deaths from the disease.